2011
DOI: 10.13057/biodiv/d120201
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in apomictic mangosteen (Garcinia mangostana) and its close relatives (Garcinia spp.) based on ISSR markers

Abstract: Sobir, Poerwanto R, Santosa E, Sinaga S, Mansyah E (2011) Genetic variability in apomictic mangosteen (Garcinia mangostana) and its close relatives (Garcinia spp.) based on ISSR markers. Biodiversitas 12: 59-63. In order to reveal phylogenetic relationship of mangosteen and several close relatives (Garcinia spp.), we employed seven ISSR dinucleotide primer systems on eleven close relatives of mangosteen and 28 mangosteen accessions from four islands in Indonesia (Sumatra, Java, Kalimantan and Lombok). ISSR ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
3
8
0
1
Order By: Relevance
“…The six RAPD primers used in this study were highly polymorphic across all the accessions, in agreement with the findings made by [26] and [19] who reported that, RAPD markers can be used effec- The genetic diversity revealed by RAPD primers considered in this study agrees with the observation made by [27]. The diversity of Garcinia species reported by [28] [29] and [30] using Inter Simple Sequence Repeat (ISSR), Isozyme and Randomly Amplified DNA Fingerprinting (RAF) markers respectively differed due to variation in efficiency of the markers [31]. Also confirmed the phylogenetic relationship of Garcinia species using Standard ITS primers.…”
Section: Discussionsupporting
confidence: 92%
“…The six RAPD primers used in this study were highly polymorphic across all the accessions, in agreement with the findings made by [26] and [19] who reported that, RAPD markers can be used effec- The genetic diversity revealed by RAPD primers considered in this study agrees with the observation made by [27]. The diversity of Garcinia species reported by [28] [29] and [30] using Inter Simple Sequence Repeat (ISSR), Isozyme and Randomly Amplified DNA Fingerprinting (RAF) markers respectively differed due to variation in efficiency of the markers [31]. Also confirmed the phylogenetic relationship of Garcinia species using Standard ITS primers.…”
Section: Discussionsupporting
confidence: 92%
“…Mangosteen tree height can reach 12 m, hardwood, rough skin, and has many branches (Napsiyah, Fitmawati & Sofiyanti 2017). According to Sobir et al (2011), can grow from low land to high land, but Garcinia spp grows inland <1.000 m ASL, meanwhile other Garcinia such as G. morella, G. picrorhiza, G. memecyloides, and G. hunsteniigrow can grow in the areas with elevation > 2,000 m ASL.…”
mentioning
confidence: 99%
“…Hence it is considered a single clone (Abdullah, Richard & Wolff 2012), although this theory is based on limited samples and population (Mansyah et al 2010). However, another study in some countries of Southeast Asia shows that the mangosteen population has shown phenotypic variations (Sobir et al 2011). Further study using genome sequencing has also shown genotypic variations in mangosteen (Mansyah et al 2010;Sobir et al 2011).…”
mentioning
confidence: 99%
“…This hypothesis is currently being tested by several researchers using molecular techniques, and most studies suggested that G. celebica was phylogenetically more distant from G. mangostana than G. malaccensis (Yapwattanaphun and Subhadrabandhu 2004;Sobir et al 2011;Abdullah et al 2012). Moreover, Nazre (2014) has recently proposed that the origin of mangosteen might be either from hybridization between different G. malaccensis cultivars or from multiple superior selections of different G. malaccensis female populations in Peninsular Malaysia.…”
mentioning
confidence: 99%